2020
DOI: 10.1007/s10967-020-07441-w
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and electrochemical studies on the complexes of urea ligands with uranyl (VI) and europium (III) in ionic liquid

Abstract: The spectroscopic and electrochemical behavior of the complex of tetraalkylurea ligands with uranyl(VI) and europium(III) in ionic liquid 1-butyl-3-methylimidazolium bis(tri-fluoromethylsulfonyl)imide ([Bmim][NTf 2 ]) was studied. As the steric hindrance of the substituent increases, the number of ligands in the [UO 2 (L) n ] 2+ complex decreases, however, Eu(III) maintains 8-coordinated complexes [Eu(L) 8 ] 3+ . The effect of urea ligands on the redox potential of Eu(III) is significantly greater than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Similar quasireversibility of other actinides and lanthanides have also been discussed elsewhere. 72,[74][75][76][77] Since the discussion along with the ligand-IL mixture would proceed with the reported literature dealing with mostly Eu(III) and U(VI), the aforementioned analysis followed those metal ions in detail.…”
Section: Cyclic Voltammogram Of Ln/an In Il Phasementioning
confidence: 99%
“…Similar quasireversibility of other actinides and lanthanides have also been discussed elsewhere. 72,[74][75][76][77] Since the discussion along with the ligand-IL mixture would proceed with the reported literature dealing with mostly Eu(III) and U(VI), the aforementioned analysis followed those metal ions in detail.…”
Section: Cyclic Voltammogram Of Ln/an In Il Phasementioning
confidence: 99%
“…[24][25][26][27][28][29][30] The liquid-liquid extraction of Ln/An using RTILs as a solvent 21,26,29,31 and/or direct dissolution of Ln/An oxides in the RTIL 25,28,[32][33][34][35][36] has gained popularity in the recent past. 31,35,37 Although there are several reports available on the U(VI) ion stability, complexation and speciation in RTILs, [38][39][40] there is no report on the Np(v) speciation in a hydrophobic RTIL except one recently published by Dong et al 41 The unusual stability of the different oxidation states of Np in a hydrophilic RTIL (namely Hbet.NTf 2 ) was reported by Long et al 42 A hydrolysis-stable complex of Np(IV), i.e., [BuMeIm] 2 [NpCl 6 ] (where BuMeIm + is 1-n-butyl-3-methylimidazolium) in a hydrophobic RTIL 43 was reported by Nikitenko et al 43 Although the Np(V) f-f transition peak position and the associated e value are known for the aqueous media, only one report is available on the complexation of Np(V) with nitrate in RTIL. 41 Our earlier studies for CCI of Np(V) with the other actinides such as U(VI) 12 or Th(IV) 11 suggested that the CCI of Np(V) with other actinides, such as U(VI) was weak and electrostatic in nature and hence, should be very much affected by the medium.…”
Section: Introductionmentioning
confidence: 99%
“…24–30 The liquid–liquid extraction of Ln/An using RTILs as a solvent 21,26,29,31 and/or direct dissolution of Ln/An oxides in the RTIL 25,28,32–36 has gained popularity in the recent past. 31,35,37 Although there are several reports available on the U( vi ) ion stability, complexation and speciation in RTILs, 38–40 there is no report on the Np(v) speciation in a hydrophobic RTIL except one recently published by Dong et al 41 The unusual stability of the different oxidation states of Np in a hydrophilic RTIL (namely Hbet.NTf 2 ) was reported by Long et al 42 A hydrolysis-stable complex of Np( iv ), i.e. , [BuMeIm] 2 [NpCl 6 ] (where BuMeIm + is 1- n -butyl-3-methylimidazolium) in a hydrophobic RTIL 43 was reported by Nikitenko et al .…”
Section: Introductionmentioning
confidence: 99%